PENGARUH DEWAN KOMISARIS, PERTUMBUHAN, PENDANAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PEMILIHAN AUDITOR EKSTERNAL (Students' Journal of Accounting and Banking, 2015)
This research is to test and analyze the effect of Board of Commissioners, the company growth, the external financing of the election, the institusional ownership and the effectiveness of Audit Comittee for external auditors on the manufacturing companies that go public in Indonesia.The population in this reseacrh are companies that includes in the manufacturing sector which is registered in the Indonesian Stock Exchange (BEI) in 2011-2013. As many as 101 companies selected sample with using purposive sampling technique. The analysis technique using logistic regression.The research results showed that BOC significant effect on the selection of the external auditor quality. While the company growth, external financing, the institusional ownership and effectiveness of Audit Comittee are not significant influence to selection of the external auditor.Keywords: Board of Commissioners, Company Growth, External Financing, Institusional Ownership, Effectiveness of Audit Comittee, Selection of External Auditors